Dialektika Hukum Islam pada Masa Awal Islam - Abdul Basith Junaidy (Al-Jinayah: Jurnal Hukum Pidana Islam, 2016)
Abstract: The dynamic and dialectical theory of Islamic law had been since the time of the Prophet Muhammad (p.b.u.h). However, the theory of Islamic law in a comprehensive form had just started at the time of al-Shafi’i, and then continuously further developed and refined by the next future jurists of different schools of Islamic law there. The theory of classical Islamic law seeks to integrate the authoritative text (nushûsh) and the role of human reason (ra’y). However, the function of the human mind is at a lower level (subordinate) and additional (subsidiary) rather than function doctrine revealed by God (nushûsh). All schools of Islamic law that had developed at that time had to conform to the model of integration that had to do certain concessions if it wanted to gain recognition as a legitimate school of law. For example, traditionalists must accept ra’y in the form of qiyâs. For this reason, the schools of Islamic law which would not accept qiyâs, it would have been out of the circulation, such as Zahiri and Hasywiyah schools.Keywords: Islamic Law, Early time of Islam, nushûsh, ra’y. Abstrak: Teori hukum Islam yang dinamis dan dialektis sudah ada sejak masa Rasulullah saw. Namun, teori hukum dalam bentuknya yang komprehensif baru dimulai pada masa al-Syafi’i, kemudian secara berkesinambungan terus dikembangkan dan disempurnakan oleh para fuqaha masa berikutnya dari berbagai mazhab hukum Islam yang ada. Teori Hukum Islam klasik berupaya mengintegrasikan antara teks otoritatif (nushûsh) dan peran nalar manusia (ra’y).  Namun fungsi nalar manusia  berada pada tingkatan yang lebih rendah (subordinatif) dan tambahan (subsider) dibanding fungsi ajaran yang diwahyukan Tuhan (nushûsh). Semua aliran hukum yang berkembang pada saat itu harus menyesuaikan diri dengan model integrasi yang ada dengan melakukan konsesi-konsesi tertentu jika ingin mendapatkan pengakuan sebagai aliran hukum yang sah. Misalnya, aliran tradisionalis harus menerima ra’y dalam bentuk qiyâs. Atas dasar itu, aliran-aliran hukum yang tidak mau menerima qiyâs, dengan sendirinya hilang dari peredaran, seperti mazhab Zahiri dan mazhab Hasywiyah.Kata Kunci: Hukum Islam, Masa Awal Islam, nushûsh, ra’y.